Positioning environment-friendly laser transfer film

By using water-based laser coatings to prepare positioning environmentally friendly laser transfer films, the problems of poor environmental protection performance and poor safety of existing solvent-based coatings are solved, and the green production of vacuum aluminum-plated packaging materials is realized, and the mechanical and high-temperature resistance of the film is improved.

CN119858400AActive Publication Date: 2025-04-22HUNAN TAILI HENGYOU TECH DEV CO LTD

Patent Information

Application Number
CN202510345346.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-24
Publication Date
2025-04-22
Estimated Expiration
2045-03-24

AI Technical Summary

Technical Problem

The existing solvent-based laser transfer coatings have problems of poor environmental protection performance and poor safety, which are difficult to meet the requirements of food packaging materials, and have low adhesion between layers and unstable fastness.

Method used

Water-based laser coatings are used to replace solvent-based coatings to prepare environmentally friendly laser transfer films, including base film layers, laser information layers and aluminum plating layers. The laser information layer is composed of aqueous polyurethane acrylic resin emulsion, photo-induced aqueous alkyd resin, dipentaerythritol hexaacrylate, etc.

Benefits of technology

It realizes green, efficient and safe production of vacuum aluminum-plated packaging materials, improves the mechanical strength and high temperature resistance of the laser transfer film, and solves the problems of environmental pollution and occupational health risks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119858400A_ABST
    Figure CN119858400A_ABST
Patent Text Reader

Abstract

The invention relates to the field of packaging materials, in particular to a positioning environment-friendly laser transfer film which is composed of a base film layer, a laser information layer and an aluminum plating layer. The laser information layer is prepared from the following raw materials in parts by weight: 60 to 70 parts of waterborne polyurethane acrylic resin emulsion, 10 to 15 parts of photo-initiation waterborne alkyd resin, 8 to 12 parts of dipentaerythritol hexaacrylate, 0.1 to 1 part of polyether modified polysiloxane surfactant, 1 to 5 parts of aminated nano titanium dioxide and 1 to 3 parts of functional additive. The water-based laser coating is used for replacing a solvent type coating to prepare the laser information layer, the problems that the solvent type coating is poor in environmental protection performance and poor in safety are effectively solved, and green, efficient and safe production of the vacuum aluminum plating packaging material is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of packaging materials, in particular to a positioning and environmentally friendly laser transfer film. Background Art

[0002] The graphics and texts produced by laser holographic technology have special effects of dazzling light, changing colors and colorful colors. Combining laser holographic technology with precision transfer technology can obtain positioning laser transfer film, which is mainly used to accurately transfer laser patterns on substrates such as paper and plastic to achieve decoration, anti-counterfeiting and environmental protection functions. Its core feature is to form dynamic color change, three-dimensional holographic and other visual effects through the principle of light interference and diffraction, and at the same time have high-precision positioning capabilities.

[0003] Currently, the commonly used laser transfer coatings are mainly solvent-based coatings. Solvent-based laser transfer coatings have the following shortcomings: ① The coating has a low solid content and contains a large amount of solvents such as alcohols, esters, and ketones. It is not environmentally friendly and unsafe, causing pollution to the production environment and the atmospheric environment, and also posing risks to the occupational health of related operators. It is difficult to meet the requirements of food packaging materials; ② Low interlayer adhesion and unstable fastness lead to easy separation between layers, especially under high temperature conditions, the fastness fluctuates more, making it difficult to control product quality; Therefore, it is necessary to develop a positioning environmentally friendly laser transfer film that can be applied to the field of vacuum aluminized packaging materials, so as to achieve green and safe production in the field of vacuum aluminized packaging materials. Summary of the invention

[0004] Purpose of the invention: In view of the above technical problems, the present invention proposes a positioning environmentally friendly laser transfer film.

[0005] The technical solutions adopted are as follows: A positioning environmentally friendly laser transfer film, consisting of a base film layer, a laser information layer and an aluminum plating layer; The laser information layer is made of the following raw materials in parts by weight: 60-70 parts of waterborne polyurethane acrylic resin emulsion, 10-15 parts of photoinitiated waterborne alkyd resin, 8-12 parts of dipentaerythritol hexaacrylate, 0.1-1 parts of polyether modified polysiloxane surfactant, 1-5 parts of amino-modified nano titanium dioxide, and 1-3 parts of functional additives; The preparation method of the photoinitiated waterborne alkyd resin is as follows: Stir 2,4-toluene diisocyanate and heat it to 60-70°C, then add an organic tin catalyst, then add a solution obtained by dissolving 4-hydroxybenzophenone in ethyl acetate, keep the temperature for reaction for 5-10 hours, then concentrate under reduced pressure, precipitate the product with ether, collect the product by filtration, and dry in vacuo to obtain an intermediate. Under nitrogen protection, add the intermediate, linoleic acid, trimethylolpropane, and phthalic anhydride to xylene, stir and heat it to 200-210°C, keep the temperature for reaction for 1-5 hours, then remove xylene by distillation under reduced pressure, cool it to 150-160°C, add trimellitic anhydride, then heat it to 180-190°C and keep the temperature for reaction for 1-5 hours, then cool it to 100-110°C, add ethylene glycol monobutyl ether, disperse it at high speed for 0.5-1 hour, and then return to room temperature.

[0006] Furthermore, the preparation method of the aqueous polyurethane acrylic resin emulsion is as follows: Add diisocyanate, 2,2-dihydroxymethylpropionic acid and polyester diol to butanone, stir and heat to 70-80°C for reaction for 1-10h, then add hydroxypropyl methacrylate, N,N-dimethylethanolamine, acrylic acid monomer and deionized water in sequence, stir well to make the mixture uniform, add free radical initiator, continue stirring and react for 1-10h, then remove butanone by reduced pressure distillation.

[0007] Furthermore, the acrylic acid monomer consists of vinyl-terminated castor oil, acrylic acid, butyl acrylate and methyl methacrylate in a mass ratio of 1-10:1-10:1-10:1-10.

[0008] Furthermore, the vinyl-terminated castor oil is obtained by esterification reaction of maleic anhydride and castor oil.

[0009] Furthermore, the preparation method of amination nano titanium dioxide is as follows: Add ethylenediamine to deionized water, add lysine and tetrabutyl titanate under stirring, adjust the pH of the reaction solution to 10-11 and continue stirring for 0.5-1h, then transfer to a hydrothermal reactor, seal and heat to 100-120°C to react for 10-20h, cool naturally to room temperature, filter and collect the product, wash and dry.

[0010] Furthermore, the mass ratio of lysine to tetrabutyl titanate is 1-5:1-5.

[0011] Furthermore, the functional additives include a defoamer, a leveling agent and an adhesion promoter.

[0012] Furthermore, the mass ratio of the defoamer, the leveling agent and the adhesion promoter is 1-5:1-5:1-5.

[0013] Furthermore, the base film layer is at least one of BOPP film, PET film, PVC film, PLA film, and PBAT film.

[0014] It has the following beneficial effects: The present invention provides a positioning environmentally friendly laser transfer film, which uses water-based laser paint instead of solvent-based paint to prepare the laser information layer, effectively solving the problems of poor environmental performance and poor safety of solvent-based paint, and realizing the green, efficient and safe production of vacuum aluminum-plated packaging materials; The water-based polyurethane acrylic resin emulsion not only takes into account the various performance characteristics that transfer coatings should have, but also overcomes the problems of environmental pollution, health hazards and safety hazards in the production of solvent-based transfer coatings. The introduced vinyl-terminated castor oil can form an alternating structure of flexible segments and rigid segments with methyl methacrylate, which can effectively improve the toughness of the coating film. The linoleic acid structure in the photo-initiated waterborne alkyd resin structure gives the coating elasticity, while the introduction of phthalic anhydride and trimellitic anhydride enhances the crosslinking density, achieving a "hard and soft" effect. The introduction of benzophenone structure not only increases the photocuring rate and improves the mechanical properties of the coating to a certain extent, but also avoids the toxicity problem caused by the residual and migration of photolytic fragments caused by the additional addition of small molecule initiators. As a hexafunctional crosslinking agent, dipentaerythritol hexaacrylate has high reactivity and forms a dense three-dimensional network structure during UV curing, thereby improving the rigidity of the coating film. The addition of polyether-modified polysiloxane surfactants can improve the wetting properties of the coating film on the base film and avoid shrinkage holes or fisheye defects during coating. The polyether segments can also combine with the amino groups on the surface of amino-modified nano-titanium dioxide through hydrogen bonds to form an adsorption layer, providing steric hindrance to prevent the agglomeration of amino-modified nano-titanium dioxide. In the photoinitiation stage, the ether bonds of the polyether segments can be used as free radical transfer agents to accelerate the crosslinking reaction of dipentaerythritol hexaacrylate and shorten the curing time. Through the flexible deformation of the polysiloxane segments, the volume shrinkage stress caused by the crosslinking of the resin during UV curing is alleviated, thereby avoiding microcracks in the aluminum coating layer due to the warping of the substrate. The amino-modified nano-titanium dioxide is uniformly dispersed in the resin matrix and improves the mechanical strength and high temperature resistance of the laser transfer film through multiple mechanisms such as nano-enhancement, interfacial bonding, photothermal synergy and environmental response. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 This is a schematic diagram of the structure of the positioning environmentally friendly laser transfer film in Example 1, where the numbers in the figure represent: 1-BOPP base film layer, 2-laser information layer, 3-aluminum coating layer. DETAILED DESCRIPTION

[0016] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially. The techniques not mentioned in the present invention are all referenced to the prior art. Unless otherwise specified, the following examples and comparative examples are parallel experiments, using the same processing steps and parameters.

[0017] Water-based polyurethane acrylic resin emulsion: homemade; Photoinitiated waterborne alkyd resin: homemade; Dipentaerythritol hexaacrylate: P-61031 (DPHA), Jining Tangyi Chemical Co., Ltd.; Polyether-modified polysiloxane surfactant: Momentive Silwet L-77, Guangzhou Xinhuateng Technology Co., Ltd. Amination nano titanium dioxide: homemade; Defoamer BYK-024: BYK, Germany, Jining Fangyu Chemical Co., Ltd.; Leveling agent BYK-346: BYK, Germany, Jining Fangyu Chemical Co., Ltd.; Adhesion promoter BYK-4500: BYK, Germany, Jining Fangyu Chemical Co., Ltd.

[0018] Embodiment 1: A positioning environmentally friendly laser transfer film, comprising a BOPP base film layer 1, a laser information layer 2 and an aluminum-plated layer 3; The laser information layer 2 is made of the following raw materials in parts by weight: 65 parts of waterborne polyurethane acrylic resin emulsion, 13 parts of photoinitiated waterborne alkyd resin, 10 parts of dipentaerythritol hexaacrylate, 0.5 parts of polyether modified polysiloxane surfactant, 4 parts of amino-modified nano titanium dioxide, 0.5 parts of defoamer BYK-024, 1 part of leveling agent BYK-346, and 1 part of adhesion promoter BYK-4500.

[0019] Wherein, the preparation method of waterborne polyurethane acrylic resin emulsion is as follows: 100g of castor oil (industrial grade, hydroxyl value 160±5mg KOH / g, Sinopharm Group), 30g of maleic anhydride, 1.5g of N,N-dimethylbenzylamine and 500ml of xylene were added to a three-necked flask with a condenser and a water separator, and the temperature was raised to 120°C for reaction for 5h. After the reaction, the room temperature was restored, 500ml of saturated sodium carbonate solution was added for washing, the organic phase was separated, and the carboxyl-terminated vinyl castor oil was obtained by vacuum concentration. 50g of isophorone diisocyanate, 12g of 2,2-dimethylolpropionic acid and 120g of polyester diol (Covestro, Desmophen, molecular weight 2000) were added to 200ml of butanone, the temperature was raised to 70°C for reaction for 10h with stirring, and then 5g of hydroxypropyl methacrylate was added. The reaction was stirred for 1h to terminate the polymerization reaction of the polyurethane, and then 8g of N, N-dimethylethanolamine was used to neutralize the carboxyl groups in the polyurethane structure, and then 5 g of vinyl-terminated castor oil, 5 g of acrylic acid, 20 g of butyl acrylate and 30 g of methyl methacrylate were added to form an acrylic monomer. After stirring for 30 min, 300 ml of deionized water was added, and phase inversion was performed at a shear rate of 2000 r / min. After 10 min, the shear rate was reduced to 60 r / min, and 1 g of free radical initiator AIBN was added. After continuing to stir the reaction for 5 h, butanone was removed by reduced pressure distillation.

[0020] The preparation method of the photoinitiated waterborne alkyd resin is as follows: 43.5 g of 2,4-toluene diisocyanate was stirred and heated to 65°C, and 0.05 g of dibutyltin dilaurate was added, followed by 49.5 g of The solution obtained by dissolving 4-hydroxybenzophenone in 300ml of ethyl acetate was added dropwise. After the dropwise addition, the mixture was kept warm for 10h and then appropriately concentrated under reduced pressure. 500ml of ether was added to precipitate the product. The product was collected by filtration and dried in vacuo at 65°C to obtain an intermediate. Under nitrogen protection, 20g of the intermediate, 42.3g of linoleic acid, 24.3g of trimethylolpropane, 24.7g of phthalic anhydride and 500ml of xylene were added to a reactor with a water separator and a condenser. The temperature was raised to 200°C and the reaction was kept warm for 4h. During this period, the water generated by the reaction was separated and the xylene was refluxed into the reactor. After the reaction, the xylene was removed by reduced pressure distillation, the temperature was lowered to 160°C, 8.7g of trimellitic anhydride was added, the temperature was raised to 180°C and the reaction was kept warm for 2h, the temperature was lowered to 100°C, 41.6g of ethylene glycol monobutyl ether was added, and the mixture was dispersed at high speed for 0.5h and then restored to room temperature.

[0021] The preparation method of amination nano titanium dioxide is as follows: Add 20 ml of ethylenediamine to 300 ml of deionized water, then add 40 g of lysine and 30 g of tetrabutyl titanate while stirring. Adjust the pH of the reaction solution to 10 with 1 mol / L sodium hydroxide solution and continue stirring for 0.5 h. Then transfer it to a hydrothermal reactor, seal it and heat it to 120 °C for 15 h. After the reaction is completed, naturally cool it to room temperature. Filter and collect the product, wash it with anhydrous ethanol and deionized water, and then dry it in a vacuum.

[0022] The preparation method of the above positioning environmentally friendly laser transfer film is as follows: Aqueous polyurethane acrylic resin emulsion, photoinitiated aqueous alkyd resin, dipentaerythritol hexaacrylate, polyether modified polysiloxane surfactant, amino nano titanium dioxide, defoamer BYK-024, leveling agent BYK-346, and adhesion promoter BYK-4500 were mixed and stirred for 10 minutes to obtain a laser transfer coating. The laser transfer coating was coated on the BOPP base film layer 1 by a high-speed coater, and then dried at 30°C for 1 hour, and then cured under ultraviolet light for 300 seconds to obtain a laser information layer 2 with a thickness of about 5 μm. The embossing plate was heated to 180°C, and the laser information on the embossing plate was hot stamped onto the laser information layer 2 under high temperature to form a laser colorful effect. The vacuum aluminum plating machine heated the aluminum wire to vaporization under a high vacuum condition of 0.04 Pa, and an aluminum plating layer 3 with a thickness of about 50 nm was formed on the laser information layer 2 by vacuum aluminum plating.

[0023] Embodiment 2: A positioning environmentally friendly laser transfer film, comprising a BOPP base film layer 1, a laser information layer 2 and an aluminum-plated layer 3; The laser information layer 2 is made of the following raw materials in parts by weight: 70 parts of waterborne polyurethane acrylic resin emulsion, 15 parts of photoinitiated waterborne alkyd resin, 12 parts of dipentaerythritol hexaacrylate, 1 part of polyether modified polysiloxane surfactant, 5 parts of amino nano titanium dioxide, 0.5 parts of defoamer BYK-024, 1 part of leveling agent BYK-346, and 1 part of adhesion promoter BYK-4500.

[0024] The preparation methods of the waterborne polyurethane acrylic resin emulsion, the photo-initiated waterborne alkyd resin and the amino-modified nano-titanium dioxide are the same as those in Example 1.

[0025] The preparation method of the above positioning environmentally friendly laser transfer film is as follows: Aqueous polyurethane acrylic resin emulsion, photoinitiated aqueous alkyd resin, dipentaerythritol hexaacrylate, polyether modified polysiloxane surfactant, amino nano titanium dioxide, defoamer BYK-024, leveling agent BYK-346, and adhesion promoter BYK-4500 were mixed and stirred for 10 minutes to obtain a laser transfer coating. The laser transfer coating was coated on the BOPP base film layer 1 by a high-speed coater, and then dried at 30°C for 1 hour, and then cured under ultraviolet light for 300 seconds to obtain a laser information layer 2 with a thickness of about 5 μm. The embossing plate was heated to 180°C, and the laser information on the embossing plate was hot stamped onto the laser information layer 2 under high temperature to form a laser colorful effect. The vacuum aluminum plating machine heated the aluminum wire to vaporization under a high vacuum condition of 0.04 Pa, and an aluminum plating layer 3 with a thickness of about 50 nm was formed on the laser information layer 2 by vacuum aluminum plating.

[0026] Embodiment 3: A positioning environmentally friendly laser transfer film, comprising a BOPP base film layer 1, a laser information layer 2 and an aluminum-plated layer 3; The laser information layer 2 is made of the following raw materials in parts by weight: 60 parts of waterborne polyurethane acrylic resin emulsion, 10 parts of photoinitiated waterborne alkyd resin, 8 parts of dipentaerythritol hexaacrylate, 0.1 parts of polyether modified polysiloxane surfactant, 1 part of amino-modified nano titanium dioxide, 0.5 parts of defoamer BYK-024, 1 part of leveling agent BYK-346, and 1 part of adhesion promoter BYK-4500.

[0027] The preparation methods of the waterborne polyurethane acrylic resin emulsion, the photo-initiated waterborne alkyd resin and the amino-modified nano-titanium dioxide are the same as those in Example 1.

[0028] The preparation method of the above positioning environmentally friendly laser transfer film is as follows: Aqueous polyurethane acrylic resin emulsion, photoinitiated aqueous alkyd resin, dipentaerythritol hexaacrylate, polyether modified polysiloxane surfactant, amino nano titanium dioxide, defoamer BYK-024, leveling agent BYK-346, and adhesion promoter BYK-4500 were mixed and stirred for 10 minutes to obtain a laser transfer coating. The laser transfer coating was coated on the BOPP base film layer 1 by a high-speed coater, and then dried at 30°C for 1 hour, and then cured under ultraviolet light for 300 seconds to obtain a laser information layer 2 with a thickness of about 5 μm. The embossing plate was heated to 180°C, and the laser information on the embossing plate was hot stamped onto the laser information layer 2 under high temperature to form a laser colorful effect. The vacuum aluminum plating machine heated the aluminum wire to vaporization under a high vacuum condition of 0.04 Pa, and an aluminum plating layer 3 with a thickness of about 50 nm was formed on the laser information layer 2 by vacuum aluminum plating.

[0029] Comparative Example 1: The same as Example 1, except that a commercially available aqueous acrylic resin emulsion (Young Sun ® AC 6038) replaces water-based polyurethane acrylic resin emulsion.

[0030] Comparative Example 2 is basically the same as Example 1, except that no photoinitiator water-based alkyd resin is added, and 1% by weight of photoinitiator 1173 of the water-based polyurethane acrylic resin emulsion is added.

[0031] Comparative Example 3: basically the same as Example 1, except that dipentaerythritol hexaacrylate is not added.

[0032] Comparative Example 4: is basically the same as Example 1, except that no polyether-modified polysiloxane surfactant is added.

[0033] Comparative Example 5: The method is basically the same as Example 1, except that commercially available nano titanium dioxide (HOMBITEC RM200) is used instead of amino-treated nano titanium dioxide.

[0034] Performance Test: The laser transfer coatings in Examples 1-3 of the present invention and Comparative Examples 1-5 were respectively coated uniformly on BOPP films with the same thickness, dried at 30° C. for 1 hour, and then cured under ultraviolet light for 300 seconds to obtain samples, and performance tests were performed on the samples.

[0035] The pencil hardness of the coating was measured using a PPH-750 pencil hardness tester from Shanghai Tianchen Modern Environmental Technology Co., Ltd. in accordance with GB / T6739-2006; The HGQ paint film cross-cutting device produced by Shanghai Pushen Chemical Machinery Co., Ltd. was used to measure the adhesion of the coating according to GB / T9268-1998; The impact resistance of the coating was measured using the BGD304 paint film impactor produced by Guangzhou Biaogeda Precision Instrument Co., Ltd. in accordance with GB / T1732-1993. Set the oven temperature to 100℃, put the sample into the oven after constant temperature, quickly close the door and start timing for 2 minutes, take out and check the appearance, if the sample has no blue or white phenomenon, it is qualified, repeat the above steps until the temperature of the sample changes, which is the high temperature resistance. The high temperature resistance of the sample is characterized by the number of times it is put into the oven.

[0036] The test results are shown in Table 1 below:

[0037] It can be seen from Table 1 above that the laser information layer in the positioning and environmentally friendly laser transfer film prepared by the present invention has excellent mechanical strength and high temperature resistance; From the comparison between Example 1 and Comparative Example 1, it can be seen that the addition of the waterborne polyurethane acrylic resin emulsion significantly improves the mechanical strength and high temperature resistance of the laser information layer; From the comparison between Example 1 and Comparative Example 2, it can be seen that the addition of the photoinitiated waterborne alkyd resin significantly improves the mechanical strength and high temperature resistance of the laser information layer; From the comparison between Example 1 and Comparative Example 3, it can be seen that the addition of dipentaerythritol hexaacrylate significantly improves the mechanical strength and high temperature resistance of the laser information layer; From the comparison between Example 1 and Comparative Example 4, it can be seen that the addition of polyether-modified polysiloxane surfactants can significantly improve the mechanical strength and high temperature resistance of the laser information layer. From the comparison between Example 1 and Comparative Example 5, it can be seen that, compared with commercially available nano titanium dioxide, the addition of amino-modified nano titanium dioxide in the present invention has a greater improvement in the mechanical strength and high temperature resistance of the laser information layer.

[0038] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A positioning environmentally friendly laser transfer film, characterized in that: It is composed of a base film layer, a laser information layer and an aluminum plating layer; The laser information layer is made of the following raw materials in parts by weight: 60-70 parts of waterborne polyurethane acrylic resin emulsion, 10-15 parts of photoinitiated waterborne alkyd resin, 8-12 parts of dipentaerythritol hexaacrylate, 0.1-1 parts of polyether modified polysiloxane surfactant, 1-5 parts of amino-modified nano titanium dioxide, and 1-3 parts of functional additives; The preparation method of the photoinitiated waterborne alkyd resin is as follows: Stir 2,4-toluene diisocyanate and heat it to 60-70°C, then add an organic tin catalyst, then add a solution obtained by dissolving 4-hydroxybenzophenone in ethyl acetate, keep the temperature for reaction for 5-10 hours, then concentrate under reduced pressure, precipitate the product with ether, collect the product by filtration, and dry in vacuo to obtain an intermediate. Under nitrogen protection, add the intermediate, linoleic acid, trimethylolpropane, and phthalic anhydride to xylene, stir and heat it to 200-210°C, keep the temperature for reaction for 1-5 hours, then remove xylene by distillation under reduced pressure, cool it to 150-160°C, add trimellitic anhydride, then heat it to 180-190°C and keep the temperature for reaction for 1-5 hours, then cool it to 100-110°C, add ethylene glycol monobutyl ether, disperse it at high speed for 0.5-1 hour, and then return to room temperature.

2. The positioning environmentally friendly laser transfer film according to claim 1, characterized in that: The preparation method of the aqueous polyurethane acrylic resin emulsion is as follows: Add diisocyanate, 2,2-dihydroxymethylpropionic acid and polyester diol to butanone, stir and heat to 70-80°C for reaction for 1-10h, then add hydroxypropyl methacrylate, N,N-dimethylethanolamine, acrylic acid monomer and deionized water in sequence, stir well to make the mixture uniform, add free radical initiator, continue stirring and react for 1-10h, then remove butanone by reduced pressure distillation.

3. The positioning environmentally friendly laser transfer film according to claim 2, characterized in that: The acrylic acid monomer consists of vinyl-terminated castor oil, acrylic acid, butyl acrylate and methyl methacrylate in a mass ratio of 1-10:1-10:1-10:1-10.

4. The positioning environmentally friendly laser transfer film according to claim 3, characterized in that: The vinyl-terminated castor oil is obtained by esterification reaction of maleic anhydride and castor oil.

5. The positioning environmentally friendly laser transfer film according to claim 1, characterized in that: The preparation method of amination nano titanium dioxide is as follows: Add ethylenediamine to deionized water, add lysine and tetrabutyl titanate under stirring, adjust the pH of the reaction solution to 10-11 and continue stirring for 0.5-1h, then transfer to a hydrothermal reactor, seal and heat to 100-120°C to react for 10-20h, cool naturally to room temperature, filter and collect the product, wash and dry.

6. The positioning environmentally friendly laser transfer film according to claim 5, characterized in that: The mass ratio of lysine to tetrabutyl titanate is 1-5:1-5.

7. The positioning environmentally friendly laser transfer film according to claim 1, characterized in that: The functional additives include defoamers, leveling agents and adhesion promoters.

8. The positioning environmentally friendly laser transfer film according to claim 7, characterized in that: The mass ratio of the defoamer, the leveling agent and the adhesion promoter is 1-5:1-5:1-5.

9. The positioning environmentally friendly laser transfer film according to claim 1, characterized in that: The base film layer is at least one of a BOPP film, a PET film, a PVC film, a PLA film, and a PBAT film.

Citation Information

Patent Citations

  • Yellow UV ink-jet ink for high-speed ink-jet printing and preparation method thereof

    CN103224732A

  • Water-soluble acrylic alkyd resin and preparation method thereof

    CN103772621A

  • Single-component light-curing colored paint as well as preparation method and using method thereof

    CN104610873A

  • Anti-fog coating, anti-fog film and preparation method thereof

    CN112391112A

  • Environment-friendly BOPP laser transfer film

    CN116587760A

Cited By

  • Electroplated metal laser full-transfer film with surface lines

    CN121022182A

  • Environment-friendly transfer film and preparation method thereof

    CN121930529A